2015
DOI: 10.1007/s00330-015-4131-3
|View full text |Cite
|
Sign up to set email alerts
|

HRCT features distinguishing pre-invasive from invasive pulmonary adenocarcinomas appearing as ground-glass nodules

Abstract: • IACs appearing as GGNs were often ≥ 12.2 mm in diameter. • IACs were often ≥ 6.7 mm in solid component diameter. • The solid components of the IACs often exhibited ≥ -192 HU. • IACs exhibited air bronchogram more frequently than AIS-MIAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
46
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 26 publications
8
46
0
Order By: Relevance
“…Furthermore, there was no statistic difference of position, shape, margin, bronchus sign, pleural indentation, vascular convergence, CT GGO , and ΔCT GGO-LP between IAC and AIS-MIA groups. These findings are consistent with the previous studies [16, 17, 38]. …”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…Furthermore, there was no statistic difference of position, shape, margin, bronchus sign, pleural indentation, vascular convergence, CT GGO , and ΔCT GGO-LP between IAC and AIS-MIA groups. These findings are consistent with the previous studies [16, 17, 38]. …”
Section: Discussionsupporting
confidence: 94%
“…In our study, binary logistic regression analyses showed that only nodule type did not interfere with both CTR and SUV max . Our data were consistent with previous reports [16, 17], that mixed GGN was more common within IAC GGN. Recently, Kakinuma et al [35] found that at least a small portion (approximately 1%) of solitary pure GGNs within 5 mm will develop into IACs or MIAs appearing as solitary mixed GGNs.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations